Effect of Magnetised Water on Chloride Ions in Trickle Irrigation - Gulja S Nair, Bharathikanna R, Dr. Sushil Kumar Bansude, Dr. Nisha R, Dr. Jyothi Narayanan (Mathematical Statistician and Engineering Applications, 2023)
Inducing biochemical reactions by applying magnetic fields can help to simulate growth and productivity of crops. The method of magneto-hydro dynamical activity of natural water is a technique of applying magnetic field to change the physical and chemical parameters of water and hence modifying the filtration and dissolving properties. This will increase the assimilation of fertilizers and nutrients in plants and also increase the soil’s ability to remove salts.Magnetic water is the water passed through a magnetic device or treated with magnetic field. The present research examines the effect of magnetic water on growth and yield of Amaranthus. The study was conducted by replicated pot experiments applying magnetically treated and normal tap water and saline water (EC=1mmhos/cm,2mmhos/cm and 3mmhos/cm) under controlled environmental conditions. A magnetic treatment device was used to induce with magnetic field of intensity 0.9360T and the irrigation water was treated with the same. The study revealed that irrigating with the magnetic water improved the plant yield significantly.